Less than 5mm — The unseen threat: A practice-led investigation into micro-plastics effects on coral reefs - Lewis, Sophie; Mortensen Steagall, Marcos (DAT Journal, 2023)
This article presents an artistic practice-led research project that asks: How can communication design be used to raise awareness about the effect of microplastics on coral reefs, encouraging a shift in the mentality of single-use plastic? The study highlights the scale of the issue of micro-plastics, where environmental pollution stemmed from the throw-away society, intending to ignite action – from micro-plastics to micro-changes. An opportunity arose to visually communicate how such a desirable product, the micro plastic, is destroying ecosystems. The project employs a reflective inquiry methodology supported by a heuristic approach, surfacing the tacit and the experiential to heighten self-awareness within the researchers' practice. This approach enables the researcher to draw connections between the subconscious and unconscious mentality, challenging the stigma and pre-existing assumptions. The project explores risograph printing, a digital screenprinting method, complimented with the use of laser cutting to encourage the reader to engage with the artefact and shift the mindset from unconscious buying patterns to become a conscious consumer. In exploring these methods, the project draws on visual inspiration through contextual knowledge. Gathering information and understanding the scale of the issue contributed to the originality and the essence of artefact. The design artefact takes the form of a risograph publication design, embracing the tactility and sustainable practices of the risograph printer in responding the research question. The artefact encompasses the essence of microplastics, uncovering the truth that lies within its aesthetic appearance. Significantly, the project is a conscious, self-reflective inquiry that contributes to the field of knowledge surrounding designing for good, and to giving the ocean personhood. It contributes to discourse about practice-led research in graphic design to engage the reader in behaviour change.